1971
DOI: 10.1021/jm00286a024
|View full text |Cite
|
Sign up to set email alerts
|

Novel substrate of adenosine deaminase

Abstract: Some 4-aminoquinolines have a high activity in the treatment of bronchial asthma13-0 and malaria, as well as having antiarrhythmic23-0 properties. Compound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

1982
1982
2003
2003

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 2 publications
0
35
0
1
Order By: Relevance
“…line conditions, as described above. Then, the ring oxygen of 3-benzyloxyl-2-alkyl-4-pyranone was replaced by a nitrogen atom via a substitution reaction with aqueous ammonia at room temperature for 48 h. The 3-benzyloxyl-2-alkyl-4-pyridinone was silylated in hexamethyldisilazane under refluxing and nitrogen gas for 2 h. After evaporation of the solvent under vacuum, the residue was redissolved in 1,2-dichloroethane and then benzyloxyethoxymethylchloride that could be replaced by (2-acetoxyethoxy)methyl bromide [361] was added in the presence of a catalytic amount of trimethylsilyl trifluoromethanesulfonate (SnCl 4 could also be used as catalyst in the alkylation reaction, but might result in separation difficulties and low yields) [362]. The resulting mixture was stirred at room temperature for 4 h and then treated with an aqueous solution saturated with sodium bicarbonate.…”
Section: -Methyl (Or Ethyl)-n-(2o-hydroxyethoxy)methyl-3-hydroxyl-4-mentioning
confidence: 99%
“…line conditions, as described above. Then, the ring oxygen of 3-benzyloxyl-2-alkyl-4-pyranone was replaced by a nitrogen atom via a substitution reaction with aqueous ammonia at room temperature for 48 h. The 3-benzyloxyl-2-alkyl-4-pyridinone was silylated in hexamethyldisilazane under refluxing and nitrogen gas for 2 h. After evaporation of the solvent under vacuum, the residue was redissolved in 1,2-dichloroethane and then benzyloxyethoxymethylchloride that could be replaced by (2-acetoxyethoxy)methyl bromide [361] was added in the presence of a catalytic amount of trimethylsilyl trifluoromethanesulfonate (SnCl 4 could also be used as catalyst in the alkylation reaction, but might result in separation difficulties and low yields) [362]. The resulting mixture was stirred at room temperature for 4 h and then treated with an aqueous solution saturated with sodium bicarbonate.…”
Section: -Methyl (Or Ethyl)-n-(2o-hydroxyethoxy)methyl-3-hydroxyl-4-mentioning
confidence: 99%
“…The antiherpetic activity of acyclovir, the acyclic analogue of guanosine, was first reported along with its synthesis in 1978 [224]. The rationale for this synthesis was the previous observation that the acyclic analogue of adenosine was a substrate for adenosine deaminase [225]. Acyclovir has potent activity against several herpesviruses (herpes simplex virus types 1 and 2, Epstein -Barr virus, and varicella -zoster virus), but is not as potent against human cytomegalovirus.…”
Section: Rationale For Chemotherapy Of Viral Infectionsmentioning
confidence: 99%
“…Since the intestinal mucosa has high levels of adenosine deaminase (Ho et al, 1980), a prodrug of 1 that is protected from deamination during absorption may be a more effective oral agent. Substitution of the 2 /-or 5'-hydroxyl of adenosine is known to lead to compounds resistant to the action of adenosine deaminase (Shah et al, 1965;Bloch et al, 1967;Schaeffer et al, 1971;Hampton et al, 1972). In an earlier report we described the synthesis and evaluation of a series of di-and tri-esters of 1, which indicated that the 2' ,3 /-diacetate provided enhanced bioavailability and water solubility, whereas the 2',5 /-and 3',5 /-diacetates showed enhanced bioavailability with diminished aqueous solubility (Jones et al, 1991).…”
Section: -Methoxypurine Arabinoside (9-[i3-d-arabinofuranosyl]mentioning
confidence: 99%